2015
DOI: 10.2298/jsc131124052a
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimization methods for solving the receptor model for chemical mass balance

Abstract: The chemical mass balance (CMB 8.2) model has been extensively used in order to determine source contribution for particulate matters (size diameters less than 10 and 2.5 µm) in air quality analysis. A comparison of the source contribution estimated from three CMB models was realized through optimization techniques, such as 'fmincon' (CMB-fmincon) and genetic algorithm (CMB-GA) using MATLAB. The proposed approach was validated using a San Joaquin Valley Air Quality Study (SJVAQS) California Fresno and Bakersfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Various studies concluded that PM 10 concentration is a strong indicator for several health effects both in India (Gupta, Karar, & Srivastava, 2007) and in other parts of the world (Braga et al, 2001). Numerous Indian researchers' works on optimizing the receptor model technique to find a holistic approach for source apportionment of particulate matter (Anu, Rangabhashiyam, Rahul, & Selvaraju, 2015;Selvaraju, Pushpavanam, & Anu, 2013). Therefore studies on these particulates is necessary for obtaining better knowledge and exposure on their behaviour and composition for improvising the monitoring and control of particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies concluded that PM 10 concentration is a strong indicator for several health effects both in India (Gupta, Karar, & Srivastava, 2007) and in other parts of the world (Braga et al, 2001). Numerous Indian researchers' works on optimizing the receptor model technique to find a holistic approach for source apportionment of particulate matter (Anu, Rangabhashiyam, Rahul, & Selvaraju, 2015;Selvaraju, Pushpavanam, & Anu, 2013). Therefore studies on these particulates is necessary for obtaining better knowledge and exposure on their behaviour and composition for improvising the monitoring and control of particulate matter.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to obtain accurate temporal and spatial distribution characteristics of PM2.5 pollution; model simulation is the most efficient way to solve the problems of spatial analysis and prediction. PM2.5 concentration prediction methods include multivariate regression methods [ 7 , 8 , 9 ], genetic algorithms [ 10 , 11 ], grey [ 12 ] and Markov models [ 13 , 14 ], and artificial neural network models (ANN) [ 15 , 16 ]. An artificial neural network model is a network composed of a large number of neurons; compared with other forecasting models, the back propagation (BP) artificial neural network (BP-ANN) model is widely used to predict air pollution levels because of its high accuracy and ability to accurately map complex nonlinear problems [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%